Biochemical and genetic analysis of Lhr, a mysterious helicase/glycosylase conserved across species - Buckley, Ryan J. (2023)
Changes to DNA structure frequently inhibit essential processes such as DNA replication. Overcoming replication blockage or collapse requires replication-coupled DNA repair enzymes that catalyse removal of aberrant DNA structures and chemically modified bases. The Lhr family of helicases are found throughout archaea, including in the Heimdall- and Nano- archaeota, and are present in several bacterial clades. This family can be divided into ‘Lhr-core’ and ‘Lhr-extended’ protein variants with the latter containing an as yet uncharacterised extended C-terminal domain.